2011
DOI: 10.1073/pnas.1105725108
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein fate is determined by USP9X-regulated monoubiquitination

Abstract: α-Synuclein is central to the pathogenesis of Parkinson disease (PD). Mutations as well as accumulation of α-synuclein promote the death of dopaminergic neurons and the formation of Lewy bodies. α-Synuclein is monoubiquitinated by SIAH, but the regulation and roles of monoubiquitination in α-synuclein biology are poorly understood. We now report that the deubiquitinase USP9X interacts in vivo with and deubiquitinates α-synuclein. USP9X levels are significantly lower in cytosolic fractions of PD substantia nigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 31 publications
2
148
0
Order By: Relevance
“…Several studies have shown that ubiquitination plays an important role in regulating α-Syn degradation by the proteasome (39)(40)(41)(42)(43)(44). Interestingly, Tofaris et al (45) showed that ubiquitination of α-Syn by Nedd4 targets it for degradation via the endosomal/lysosomal pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that ubiquitination plays an important role in regulating α-Syn degradation by the proteasome (39)(40)(41)(42)(43)(44). Interestingly, Tofaris et al (45) showed that ubiquitination of α-Syn by Nedd4 targets it for degradation via the endosomal/lysosomal pathway.…”
Section: Resultsmentioning
confidence: 99%
“…and (iii) this DUB is capable of removing monoubiquitins as well as polyubiquitin chains of different topologies from quite a number of proteins (71)(72)(73)(74), it seems likely that the list of biological pathways in which USP9X is involved will grow in the future.…”
Section: Usp9x Deubiquinates Monoubiquitinated Pex5mentioning
confidence: 99%
“…32 Although our findings implicate USP9X in the inhibition of oligodendrocytic differentiation of NSCs within the SGZ, there are caveats to this interpretation of the data. Firstly, although we noted a correlation between Usp9x-deficiency and the production of oligodendrocytes, the data presented here does not confirm that the absence of USP9X in NSCs directly leads to their differentiation into oligodendrocytes.…”
Section: E1235524-4mentioning
confidence: 48%